ANALISIS KARAKTERISTIK DAN TINGKAT PENDAPATAN USAHATANI BAWANG MERAH DI SULAWESI TENGAH - Dewi Nur Asih (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
Cultivation of shallot as a prioritized commodity has been well developed by farmers in Sulawesi Tengah.  The research aim was to determine the feasibility of ‘Palu’ shallot farming system based on the farming system description and the farmers’ income level generated from it.  The research was conducted in Donggala regency, Central Sulawesi from September to November using a survey method.  The farming system of ‘Palu’ shallot was still traditionally managed in which household members were involved in all activities of the farming system.  The land area hold in average was 0.52 ha per farmer with which the farmer could generate their income as much as IDR 7,214,792.9. The ‘Palu’ shallot farming system is financially still feasible to be developed based on its B/C ratio value of 2.73